Procedimento para análise de amortecimento de barras de pulverização de um pulverizador autopropelido - Fath, Fábio Rogério (2024)
With the increase in demand for food in the world, it is necessary for the emergence of new technologies and agricultural machines that are capable of increasing the productivity and efficiency of crops. Therefore, this work developed a procedure capable of measuring the displacement of spray bars of a self-propelled vehicle in order to enable the change of hydraulic parameters to improve damping and thus reduce the transfer of agricultural pesticides when the equipment faces acceleration and braking or obstacles during the work period. To achieve this, a process was developed based on photogrammetry with image capture to determine displacements, where a camera was positioned on the structure of the self-propelled vehicle and reference points were positioned on the spray bar. At the same time, a pressure gauge was used to check the impacts on the machine's hydraulic system. To determine the displacements, the image filter method was used, applied through software developed in partnership with the Stara company's software development team. By applying the proposed methods, it was possible to detect variations in the displacement of the spray bar, with a maximum error of 7.1mm, making the procedure suitable for the application.